The Influence of Leadership Style on Employee Performance at the De Paviljoen Hotel Bandung - Suryani, Herni; Suprianto Ahmadi, Rudi; Tisna Amijaya, Dodi; Setiadiwibawa, Luthfi (Greenation International Journal of Law and Social Sciences, 2023)
The main problem in this study is the performance of employees at the De Paviljoen Bandung hotel. This problem is thought to have arisen because the leadership style applied has not met expectations. The method used in this study was an explanatory survey, in which the population measured was De Paviljoen Bandung hotel employees, totaling 92. Then a sample of 48 was taken using the Proportionate Random Sampling method. This study shows that leadership style has a positive and significant effect on employee performance. That is, leadership style is one of the factors that can encourage increased employee performance at Hotel De Paviljoen Bandung. Increasing leadership styles, especially transactional leadership styles, can improve employee performance, especially on employee job knowledge. The good thing about the leadership style at Hotel De Paviljoen is the level of firm decision making. Meanwhile, the performance that has been good and can be maintained is the level of ability of employees who can always cooperate with colleagues. On the other hand, the leader's ability to govern employees, the level of encouragement for the development of subordinates, and the level of clarity of task structure at work need to be improved. In terms of performance, it is necessary to increase the ability to complete work in accordance with the amount of work, skills, ideas and creativity. Another thing that needs to be improved is attendance and how to work according to a predetermined work schedule.